STUDENT TEACHERS’ CONCEPTIONS OF EXPERIENCED TEACHER - Badriah, Badriah (Linguists : Journal of Linguistics and Language Teaching, 2018)
This study presents a case study of student teacher’s conceptions of experienced teacher who acts as mentor during preservice teacher education program. There were two student teachers participated in the study. They underwent preservice teaching for three months. The study provides insights into how student teacher see experienced teacher and how they take advantage this knowledge into their teaching practice. Data collection consisted of interviews and classroom observations.  Findings suggest that student teachers consider experienced teacher as: 1) an accomplished teacher who gives instruction in an effective way, 2) a role model in personal and social performance, 3) a person who knows standard of teaching and 4) an inspiring personal who helps promote student teacher personal trait. These findings direct to the quality of teacher’s work related to professional, pedagogical, personal, and social competence. This study suggests that preservice teacher education program needs to be lengthen to allow the student teacher gain more experience and have more time to acquire competences so that they are ready to be a real teacher.